2009
DOI: 10.1080/03009740802448866
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory role of nerve growth factor and its receptor system in fibroblast‐like synovial cells

Abstract: Upregulation of NGF/TrkA in proinflammatory cytokine-activated FLS, the mitogenic effect of NGF on FLS, and the increased NGF level in SF of inflammatory arthritis suggest that there is cross-talk between NGF/NGF-R and FLS. These results also suggest that dysregulated production of NGF may lead to synovial cell proliferation and thus could influence the inflammatory and proliferative cascades of inflammatory arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…19,28 NGF receptor (NGF-R) (TrkA and p75) were expressed in synoviocytes (Fig. 2C), in line with the previous study, 29,30 NGF and NGF-R were unregulated in synoviocytes of patients with rheumatoid arthritis or spondyloarthritis.…”
Section: Characterization Of Synoviocytessupporting
confidence: 87%
“…19,28 NGF receptor (NGF-R) (TrkA and p75) were expressed in synoviocytes (Fig. 2C), in line with the previous study, 29,30 NGF and NGF-R were unregulated in synoviocytes of patients with rheumatoid arthritis or spondyloarthritis.…”
Section: Characterization Of Synoviocytessupporting
confidence: 87%
“…Furthermore, they reported that ST-derived fibroblast-like synoviocytes (FLSs) did not produce NGF in vitro . In a recent publication, we observed similarly that NGF levels in SF were significantly higher in patients with psoriatic arthritis (PsA) (365.5 ± 85.2 pg/mL) or RA (120 ± 35 pg/mL) than in patients with osteoarthritis (OA) (30 ± 6 pg/mL) [2]. However, in regard to the source of NGF, we observed that FLSs produced a significant amount of NGF.…”
supporting
confidence: 54%
“…The overall cell growth was determined using the colorimetric MTT (3-[4,5-dimethylthiazol-2yl] diphenyltetrazolium bromide) assay [14]. Exponential phase cells were seeded in 96-well plates (5 × 10 4 cells/well) and allowed to attach overnight at 37 • C in a humidified atmosphere containing 5% CO 2 .…”
Section: Cell Viability and Apoptosismentioning
confidence: 99%